CAR‐T cells in the treatment of multiple myeloma: an encouraging cell therapy - Yu, Tong; Jiao, Jian-Hang; Wu, Min-Fei (Frontiers in Immunology, 2025)
Multiple myeloma (MM) is a malignant disease of plasma cells that accounts for approximately 10% of all hematological malignancies and is characterized by a clonal proliferation of malignant plasma cells in the bone marrow. Numerous therapeutic strategies, including proteasome inhibitors, immunomodulators, monoclonal antibodies against CD38 and autologous stem cell transplantation, have prolonged the median survival of MM patients. Nevertheless, almost all MM patients suffer disease relapses due to drug resistance and eventually die from MM or MM-related complications. Chimeric antigen receptor (CAR) T-cell therapy is a novel immunotherapy strategy for MM and has shown encouraging results in several clinical trials. However, the use of CAR T-cell therapy for the treatment of MM is still associated with several difficulties, including antigen escape, poor persistence, an immunosuppressive microenvironment, cytokine release syndrome, immune effector cell-associated neurotoxicity syndrome, CAR T-cell-associated encephalopathy syndrome, cytopenia, and infections. In this review, we describe in detail the target antigens of CAR T cells in MM. We also comprehensively discuss recent innovations in the development of CAR T cells to improve clinical efficacy and strategies to overcome the limitations of CAR T-cell therapy in MM.